Effect of formaldehyde on bile acid metabolism in HepG2 cells - Xi-chong LIU; Qing TAN; Xue-xia JIANG (Editorial Office of Chinese Journal of Public Health, 2022)
Objective To observe the effect of formaldehyde (FA) on bile acid synthesis and efflux in human hepatoma HepG2 cells and the mechanism of FA-induced hepatocyte injury. MethodsHepG2 cells were treated with FA at various dosages: 0.02, 0.10, 0.25, and 0.50 mmol/L to detect cell viability with methyl thiazolyl tetrazolium (MTT) assay after 12, 24, and 48 hours' treatment; 0.05, 0.10, and 0.20 mmol/L to detect total bile acid (TBA) in the HepG2 cells with chemical-enzymatic method after 24 and 48 hours' treatment; 0.05, 0.10, and 0.20 mmol/L to detect mRNA expressions of genes related to intracellular bile acid synthesis (including cholesterol 7α-hydroxylase [CYP7A1], sterol 12α-hydroxylase [CYP8B1], liver X receptor [LXR], farnese X receptor [FXR], small heterodimer chaperone [SHP], and bile acid efflux related gene [BSEP]) with real-time quantitative PCR after 12, 24, and 48 hours' treatment; and 0.05, 0.10, and 0.20 mmol/L to detect expressions of intracellular bile acid synthesis related protein CYP7A1 and SHP with Western blot after 12, 24, and 48 hours' treatment. The HepG2 cells of negative control were treated with Dulbecco's modified Eagle's medium (DMEM) and those of positive control were treated with 1 mmol/L oleic acid (OA) or brefeldin A (BFA) at dosages of 0.50 and 2.5 μg/ml, respectively. ResultsCompared to that of negative control cells, the viability of HepG2 cells with treatments of 0.10 - 0.50 mmol/L FA decreased significantly (P < 0.05). In comparison with those in negative control HepG2 cells, significantly increased intracellular TBA, mRNA expressions of CYP7A1, CYP8B1, and FXR, expression of CYP7A1 protein were detected in the HepG2 cells with 24 hours' treatment of 0.10 or 0.20 mmol/L FA (P < 0.05 for all); significantly increased mRNA expression of BSEP was also detected in the HepG2 cells with 24 hours' treatment of 0.20 mmol/L FA (P < 0.05). Conclusion Formaldehyde at certain dosages could significantly inhibit the viability of HepG2 cells and increase the content of bile acid in HepG2 cells; the mechanism of those effects may be related to the promoted expression of CYP7A1 and CYP8B1 in hepatocytes.